NOTES ON THE NOMENCLATURE AND THE TYPE LOCALITIES OF HOVER WASPS (INSECTA, HYMENOPTERA, VESPIDAE, STENOGASTRINAE) DESCRIBED AFTER 1999, WITH A REVISED SPECIES CHECKLIST - Jun-ichi Kojima; Fuki Saito-Morooka (BRIN Publishing (Penerbit BRIN), 2025)
Availability under the International Code of Zoological Nomenclature (“the Code”) of the species-group names of hover wasps (vespid subfamily Stenogastrinae) described after 1999 is assessed. All names are proved to be available, though some of them are dubious in their availability if we apply unusually strictly the regulation on the depository of name-bearing type specimens in the Code. Their name-bearing type specimens are commented and discussed from the point of suitability of the “type locality” in the modern taxonomic work. They are also commented from the point of view of the Convention on Biological Diversity (CBD) and the Nagoya Protocol on Access to Genetic Resources and the Fair and Equitable Sharing of Benefits Arising from their Utilization (ABS). A revised species checklist of the Stenogastrinae is given as an appendix.